Correlation between Cu ion migration behaviour and deNOx activity in Cu-SSZ-13 for the standard NH3-SCR reaction. Issue 36 (14th April 2016) - Beale, A. M.; Lezcano-Gonzalez, I.; Slawinksi, W. A.; Wragg, D. S.
Abstract : Here we present the results of a synchrotron-based in situ, time-resolved PXRD study during activation of two Cu-SSZ-13 catalysts under O2 /He and one during standard NH3 -SCR reaction conditions to obtain insight into the migration behaviour of Cu ions. Abstract : Here we present the results of a synchrotron-based in situ, time-resolved PXRD study during activation of two Cu-SSZ-13 catalysts under O2 /He and one during standard NH3 -SCR reaction conditions to obtain insight into the behaviour of Cu ions. The results obtained indicate that deNO x activity is inexorably linked with occupancy of the zeolite 6r.